Hydrogeomorphic indicators of wetland health inferred from multi-temporal remote sensing data for a new Ramsar site (Kaabar Tal), India - Manudeo Singh; Rajiv Sinha (Ecological Indicators, 2021)
Wetlands form an important and dynamic ecosystem, and therefore, need continuous monitoring. We have developed a framework to assess the status of wetland health based on hydrogeomorphic characteristics and vegetation dynamics and have implemented it on a newly designated Ramsar site, Kaabar Tal, a large floodplain wetland in Ganga Plains, eastern India. The study has attempted to integrate the hydrological, geomorphological, and ecological concepts and tools to develop the protocols for a hydrogeomorphic assessment of wetland health. We have used multi-temporal Landsat imageries to define several health indicators based on water-spread area, geomorphology, and vegetation and have integrated them to compute wetland health index (WHI) scores. These health indicators correspond to a range of spatial scales – landscape (wetland) scale, ecosystem (sub-wetland) scale, and local (pixel) scale and individually represent different hydrogeomorphic and ecological functions as well as dynamics of a wetland. We have also presented four different wetland health scenarios based on dominating health indicator and two integrated scenarios representing the best and the worst WHI scores in all four scenarios. Our results show that the Kaabar Tal is in a degraded state and the degree of degradation varies spatially within the wetland. Agriculture is the prime factor for its degradation, augmented by decreasing rainfall and anthropogenic drainage reorganization. Based on our data analysis, we have suggested several recommendations to restore the health of this wetland. The framework presented in this work has a potential to understand the relationship between hydrodynamics and ecological functions in wetland systems in different hydro-climatic settings.